Development and validation of an Age-related Language Decline Scale (ALDS) for older adults - Xinan Zhou; Yanping Dong (Acta Psychologica)
Objectives: Language decline in older adults poses a great threat to their independence. A self-report scale designed to measure age-related language decline could be very efficient, but it is still lacking. Thus, the study aimed to develop an Age-related Language Decline Scale (ALDS) for older adults. Methods: Altogether, 287 older adults aged between 65 and 80 years were recruited. They completed a scale consisting of production and comprehension subscales generated from prior research, focus group discussions and expert review. The two subscales were submitted to item analysis, exploratory and confirmatory factor analysis (EFA & CFA), internal consistency and test-retest reliability test. Criterion-related validity was assessed by correlating scale scores with participants' performance in language tasks. Results: EFA and CFA results are consistent with the literature which identified memory and inhibition as essential mechanisms of age-related language decline. The internal consistency (for both production and comprehension subscales, Cronbach's α = 0.80) and test-retest reliability (for the full scale, r = 0.80) were well above acceptable levels. The scale also demonstrated satisfactory criterion-related validity, as evidenced by significant correlations between the scale scores and participants' language performance. Conclusions: The 16-item ALDS is an effective psychometric scale for assessing age-related language decline in older adults.